Acceleration Frequency Characteristics of the Freight-Train-Induced Vibration of the Beijing-Harbin Railway Subgrade - Yingying Zhao; Xianzhang Ling; Ziyu Wang; Weiming Gong; Guoyu Li (Shock and Vibration)
The vibration acceleration during a freezing period was monitored in the Beijing-Harbin railway subgrade, and its frequency characteristics were studied. The results show the following. (1) The vibration acceleration frequency of the railway subgrade was divided into three main bands: the first frequency band is caused by the vehicle wheelbase, the second frequency band is caused by the sleeper spacing, and the third frequency band is mainly affected by the track irregularity spectrum and site structure. (2) The fitted dominant frequency, as can be seen from the monitored results, is in good agreement with the calculated value from the vibration frequency calculation formulas. (3) From the monitoring, it can be seen that train type, traveling speed, and train formation have a significant influence on the dominant frequencies of the first and second bands. Train formation, load, and distance from the track have a great influence on the amplitude of each frequency band.